2014
DOI: 10.2319/071614-497.1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of maxillary protraction using a hybrid hyrax-facemask combination: A controlled clinical study

Abstract: Objective: To evaluate the treatment effects of a hybrid hyrax-facemask (FM) combination in growing Class III patients. Material and Methods: A sample of 16 prepubertal patients (mean age, 9.5 6 1.6 years) was investigated by means of pre-and posttreatment cephalograms. The treatment comprised rapid palatal expansion with a hybrid hyrax, a bone-and toothborne device. Simultaneously, maxillary protraction using an FM was performed. Mean treatment duration was 5.8 6 1.6 months. The treatment group was compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 28 publications
1
26
2
4
Order By: Relevance
“…Several clinical studies and case reports with different treatment protocols have combined this hybrid hyrax with facemasks for maxillary protraction in Class III patients [48,[54][55][56]69]. Some of these studies [54][55][56] demonstrated advancement of the maxillary complex by statistically significant amounts which, due to the extraoral forces from facemasks, were larger than reported in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Several clinical studies and case reports with different treatment protocols have combined this hybrid hyrax with facemasks for maxillary protraction in Class III patients [48,[54][55][56]69]. Some of these studies [54][55][56] demonstrated advancement of the maxillary complex by statistically significant amounts which, due to the extraoral forces from facemasks, were larger than reported in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…In 2 of the studies the skeletal anchorage device consisted of microscrews [2023], while the remaining 7 used miniplates [14,19,21,22,2426]. As regards the location of the miniplates and miniscrews in the craniofacial structures, Şar et al [19] placed miniplates at the level of the maxillary part of the lateral nasal wall and in the symphysis mentalis.…”
Section: Resultsmentioning
confidence: 99%
“…Cha & Ngan [24] placed them at the level of the zygomatic process, while other authors [14,21,22,25] situated them in this area and in the mandible between the lateral incisors and the lower canines. For their part, Niemkemper et al [20] positioned miniscrews on both sides of the mid-palatal suture and Ge et al [23] set them in the zygomatic arch. Lastly, Koh & Chung [26] did not specify the position of the miniplates on the maxilla.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations